Plague - Grácio, A. J.Dos Santos (2017)
Plague, in the Middle Ages known as Black Death, continues to occur at permanent foci in many countries, in Africa, Asia, South America, and even the USA. During the last years outbreaks were reported from at least 3 geographical areas, in all cases after tens of years without reported cases. The recent human plague outbreaks in Libya and Algeria suggest that climatic and other environmental changes in Northern Africa may be favourable for Y. pestis epidemiologic cycle. If so, other Northern Africa countries with plague foci also may be at risk for outbreaks in the near future. It is important to remember that the danger of plague reoccurrence is not limited to the known natural foci, for example, those of Algeria, Angola, and Madagascar. In a general context, it is important that governments know the dangerous impact that this disease may have and that the health and medical community be familiar with the epidemiology, symptoms, treatment, and control of plague, so an appropriated and timely response can be delivered should the worst case happen. Plague can be used as a potential agent of bioterrorism. We have concluded that plague is without a doubt a reemerging infectious disease.